The application of real options to renewable energy investments in South Africa: the case of solar energy technology for small businesses and individual homeowners - Markham, Paul (Department of Finance and Tax, 2019)
There is a growing interest in renewable energy generation projects due to environmental and sustainability concerns. However, initial costs and uncertainties caused by a number of factors can render renewable energy projects unattractive when subject to conventional financial assessment. The overall benefits of renewable energy technologies are often not well understood and consequently are often evaluated to be less effective than traditional technologies. From the moment that the energy sector abroad started a deregulation process, with a high level of competitiveness and associated increased market uncertainty, traditional evaluation techniques became insufficient to properly deal with these additional risk and uncertainty factors. Consequently, the way investors evaluate their investments require more sophisticated evaluation techniques. Initial research suggests that the value of renewable energy projects can be enhanced by the application of real options theory. In addition to revealing the benefits that renewable energy projects provide when employing real options, analytical results indicate that real option analysis is a highly effective means of quantifying how policy planning uncertainty, including managerial flexibility, influences renewable energy development. However, real option literature regarding renewable energy generation projects is limited and the theory requires further development to take advantage of more flexibility value within renewable energy projects. Literature is particularly limited in terms of small businesses and individual homeowners and worthy of analysis. This study attempts to address this issue. This study shows that real option analysis is useful, in the face of numerous uncertainties, in assisting South African homeowners and small businesses in the six largest metros and Eskom when considering an investment in a solar PV system. Within these six metros and Eskom three different tariff structures are offered, some of which encourage such investments while others don’t, thus forcing the latter to purchase expensive battery systems and consequently making the investment somewhat ineffective. Investments in solar PV systems are relatively costly and so, before committing, one needs to be certain that the system will be cost effective. In this study, it is shown that there is strong evidence that real option analysis is, not only useful in determining whether such an investment is cost effective, but also in assisting with the timing of such investments. This could be crucial for success. The findings of this study have theoretical implications in terms of the efficiency of real option analysis in the South African energy sector, and thus provide a contribution to real option literature in this sector. They also have practical insights for investors, both homeowners and small businesses in the South African context, who are looking to invest in a solar PV system. The study starts with an introduction and background to energy generation and then presents a literature review concentrating on the use of real options as an appropriate valuation method for renewables. Thereafter, the hypothesis is stated and the data sample and research methodology discussed. One of the limitations of this study was the unreliable data and the difficulty finding it, which could give rise to self-selection bias. Finally, the results and a brief analysis are presented and then, in conclusion, there is a discussion on the limitations of the study and suggestions for further research.